2020
DOI: 10.1021/acs.chemrev.9b00830
|View full text |Cite
|
Sign up to set email alerts
|

Water in Nanopores and Biological Channels: A Molecular Simulation Perspective

Abstract: This Review explores the dynamic behavior of water within nanopores and biological channels in lipid bilayer membranes. We focus on molecular simulation studies, alongside selected structural and other experimental investigations. Structures of biological nanopores and channels are reviewed, emphasizing those high-resolution crystal structures, which reveal water molecules within the transmembrane pores, which can be used to aid the interpretation of simulation studies. Different levels of molecular simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 481 publications
(855 reference statements)
5
124
0
Order By: Relevance
“…Their pores are completely filled with water molecules. Molecular simulations show that water diffuses more slowly than in bulk, probably owing to the strong structuration of water within the pores, similar to what is observed in carbon nanotubes (CTNs) [7e] …”
Section: Aquaporins and Porinssupporting
confidence: 53%
“…Their pores are completely filled with water molecules. Molecular simulations show that water diffuses more slowly than in bulk, probably owing to the strong structuration of water within the pores, similar to what is observed in carbon nanotubes (CTNs) [7e] …”
Section: Aquaporins and Porinssupporting
confidence: 53%
“…However these structural changes of water have to be challenged under non-equilibrium conditions such as electrical fields, osmotic and hydrostatic pressure [32][33][34] . A coarse-grain approach 35,36 applied to the specific treatment of synthetic materials would be necessary to access significantly longer timescales and to probe scalability for the future applications in inverse osmosis and ultrafiltration devices 37,38 . FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Since experimental measurement about confined molecule properties in the nanoscale is difficult ( Rodríguez-Vázquez et al, 2017 ), molecular dynamics (MD) simulations play a key role in the description of these systems ( Lynch et al, 2020 ). Recent studies carried out in our group showed that α,δ-SCPNs are stable and theoretically able to translocate water and cations when inserted into a lipid bilayer ( Calvelo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%